All the Oedipus, Oedipus. Some notes on the translation of Sophocles’ Oedipus Rex (El Hilo de la Fabula, 2022)
In the present work I will present some problems related to the translation into Spanish of Oedipus Rex, by Sophocles, especially in relation to what the appropriation of the work from the language itself implies. To this end, after introducing a series of general considerations on the translation of classical texts in general, I will present some examples in which the mentioned difficulties appear.
Keywords: Oedipus Rex; translation; hermeneutics